Comparison of mechanochemical ablation versus ligation and stripping for the treatment of incompetent small saphenous vein. (February 2022) - Apruzzi, Luca; Bilman, Victor; Ardita, Vincenzo; Favia, Nicola; Saracino, Concetta; Chiesa, Roberto; Baccellieri, Domenico
Objective: to compare the outcomes of mechanochemical ablation (MOCA) versus saphenopopliteal junction ligation and stripping (OS) for symptomatic small saphenous vein (SSV) insufficiency. Methods: This is a retrospective study including symptomatic SSV patients treated with MOCA using the ClariVein catheter (Merit Medical, South Jordan, Utah, USA) or OS from 2015 to 2019. Results: A total of 60 limbs (73.3% women, mean age 54.7 ± 14.4 years) were treated with MOCA and 58 limbs (63.8% women, mean age 54 ± 11.6 years) with OS. At 18 months follow-up, recurrence rates were 7.5% (4/53) for MOCA vs. 5.7% (3/52) for the OS group. MOCA group was associated with less pain at first postoperative day, and an early return to work (MOCA 3.5 ± 2.3 days vs. OS 14.2 ± 3.8 days, p < .0001). No cases of leg paresthesia/dysesthesia were observed in the MOCA group, while two patients (3.4%) presented neurological symptoms after OS treatment. Conclusion: MOCA and OS are both safe and effective techniques for symptomatic SSV insufficiency. MOCA group demonstrated to be associated with less postoperative pain and early return to work compared to OS.